Imprints of Climate Signals in a 204 Year δ18O Tree-Ring Record of Nothofagus pumilio From Perito Moreno Glacier, Southern Patagonia (50°S) - Grießinger, Jussi; Langhamer, Lukas; Schneider, Christoph; Saß, Björn-Lukas; Steger, David; Skvarca, Pedro; Braun, Matthias H.; Meier, Wolfgang J.-H.; Srur, Ana M.; Hochreuther, Philipp (Frontiers in Earth Science, 2018)
A 204 year-long record of 18O in tree-ring cellulose of southern beech (Nothofagus pumilio) from a site near Perito Moreno Glacier (50°S) in southern Patagonia was established to assess its potential for a climate reconstruction. The annually resolved oxygen isotope chronology is built out of seven individual tree-ring 18O series with a significant mean inter-series correlation (r = 0.61) and is the first of its kind located in Southern America south of 50°S. Over a common period from 1960 to 2013 of available stationary and high-resolution gridded CRU TS v. 4.01 data, the 18O chronology exhibits a strong sensitivity towards hydroclimatic as well as temperature parameters as revealed by correlation analyses. Among these, positive correlations with maximum temperature in the first part of the summer season (CRU rONDJ = 0.51, p<0.01) and negative correlations with precipitation in the latter half of the vegetation period (CRU rONDJ = - 0.54, p<0.01) show the highest sensitivities. A strong supra-regional influence of the Southern Annular Mode (SAM) is clearly recorded in this chronology as indicated by significant positive correlations during the vegetation period (rONDJ = 0.62, p<0.01). This indicates that the presented 18O-chronology shows great promise to reconstruct the influence and variability of the SAM within the last two centuries in southern South America. The modulation of positive and negative anomalies within this series can be interlinked to changes in moisture source origin as revealed by backward trajectory modeling. Additionally, these anomalies can be directly associated to positive or negative phases of the Antarctic Oscillation Index (AAOI) and therefore the strength of the Westerlies. Aligned by the analysis on the influence of different main weather types on the 18O chronology it is shown that such time-series hold the potential to additionally capture their respective influence and change during the last centuries.